Strengthening the build-operate-transfer law for the development of Philippine infrastructure to improve competitiveness in the light of the ASEAN integration: Amending the law to plug its weakness and be aligned with the principles of the ASEAN PPP framework - Tiu, Andrew Michael (Animo Repository, 2015)
The ASEAN Integration of 2015 is now here. However, according to the World Economic Forum in 2014, poor infrastructure has overtaken corruption as the most problematic factor in the Philippines. In 1994, Congress amended the Build Operate Transfer Law in order to jump start the country's development. Despite the passage of the law, the country has not seen a major improvement in infrastructure for the last 20 years. In addition, the government encountered two major failures in the implementation of two big BOT projects - the Ninoy Aquino Terminal 3 infrastructure and the Metro Rail Transit 3 infrastructure. The reason for these failures are numerous namely lack of competence of public officials, lack of accountability, lack of clear dispute mechanism, and lack of a clear project termination policy. The current PPP law as it stands has full of weaknesses and loopholes. There is a need to provide more accountability on public officers handling the projects. There is a need to have a clear termination policy including cases where PPP contracts are declared null and void. There is a need to provide a clear Alternative Dispute Resolution process. Finally, there is a need to align the PPP Law with other infrastructure procurement regulations connected with PPP such as the Government Procurement Act (RA 9184) and the Electric Power Industry Reform Act (EPIRA). One of the major thrust of the Aquino Administration is the use of the Public-Private Partnership in the development of the country's infrastructure. To that end, he expanded the powers of the PPP Center. His administration work with the Australian Government in order to create a new fund which will be used to prepare PPP projects which is called the Project Development and Monitoring Fund. In 2012, the administration was able to release an amended Implementing Rules and Regulation of the BOT law in order to cover the loopholes and not to repeat the problems that plague the NAIA 3 BOT project. He also instituted the PPP Governing Board which will be the major policy making body on PPP projects. In the three years, the PPP Center was able to successfully able to produce a pipe line of 61 PPP projects costing about Php 1,212.26 billion pesos. Due to the hard work of the PPP Center, it won the Gold Award as the Best Central Government Promoter at the 2014 Partnerships Awards. This recognition help boost the Philippines stature with international investors. Looking forward to the future, the administration is looking forward to the passing of the new law called the PPP Act which would amend the current BOT Law. On December 2014, ASEAN released a framework called ASEAN Principles on PPP Framework in order to achieve the ASEAN vision of physical infrastructure integration. With the release of this PPP Framework, there is a need to examine the proposed PPP Act on whether it is consistent with the ASEAN Framework. The ASEAN PPP Framework seeks to bridge the infrastructure gap in the ASEAN region. It also highlights the importance of an enhanced infrastructure base as a critical prerequisite to fostering economic and social development and regional connectivity. By aligning the Proposed PPP law to the Framework, the PPP Act will be more responsive not only to the country's infrastructure needs but also on meeting the vision of the ASEAN Integration.